Handbook of Psychology 2003
DOI: 10.1002/0471264385.wei0505
|View full text |Cite
|
Sign up to set email alerts
|

Psychodynamic Models of Personality

Abstract: This chapter discusses the evolution of psychodynamic models of personality, and the place of these models within contemporary psychology. After reviewing the core assumptions of psychoanalysis—primacy of the unconscious, psychic causality, and the critical importance of early experiences—the basic elements of Freud's classical psychoanalytic theory are described, including the drive model, topographic model, psychosexual stage model, and structural model. Neo‐analytic theories, object relations theory, self‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The general idea that motivated repression may contribute to conscious self-representation has had a long and checkered history (Freud, 1926;Gur & Sackeim, 1979;McCrae & Costa, 1983;Paulhus & John, 1998;Shedler, Mayman, & Manis, 1993). Rather than assuming that explicit/ implicit mismatches necessarily reflect motivated repression, we take a more agnostic view by simply assuming that explicit and implicit components of personality reflect different operations of mind and may therefore diverge for this simple reason (Bornstein, 2003;Greenwald & Banaji, 1995;McClelland et al, 1989;Robinson et al, 2003a).…”
Section: Prior Research On Agreeableness Implicit Self-esteem and Nmentioning
confidence: 99%
See 2 more Smart Citations
“…The general idea that motivated repression may contribute to conscious self-representation has had a long and checkered history (Freud, 1926;Gur & Sackeim, 1979;McCrae & Costa, 1983;Paulhus & John, 1998;Shedler, Mayman, & Manis, 1993). Rather than assuming that explicit/ implicit mismatches necessarily reflect motivated repression, we take a more agnostic view by simply assuming that explicit and implicit components of personality reflect different operations of mind and may therefore diverge for this simple reason (Bornstein, 2003;Greenwald & Banaji, 1995;McClelland et al, 1989;Robinson et al, 2003a).…”
Section: Prior Research On Agreeableness Implicit Self-esteem and Nmentioning
confidence: 99%
“…This approach, while certainly capturing important aspects of personality, can never be exhaustive of it (Epstein, 1994;McClelland, 1987;Westen, 1995). Implicit processing tendencies also vary between individuals and have relevance to cognitions, emotions, and behavior (Bornstein, 2003;Greenwald & Banaji, 1995;Kelly, 1963;Robinson & Neighbors, 2006). Historically, unconscious aspects of personality have often been operationalized in terms of projective tests of motivation (e.g., the Thematic Apperception Test [TAT]; McClelland, 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Decades of research on TAT-based assessments of motivation have indicated that such assessment measures are reliable and valid but largely unrelated to self-reports of motivation (Bornstein, 2003;McClelland, Koestner, & Weinberger, 1989;Spangler, 1992;Winter, John, Stewart, Klohnen, & Duncan, 1998). Why so?…”
Section: Toward a Cognitive Science Of Motivationmentioning
confidence: 99%
“…This application is particularly relevant as personality pathology is increasingly defined as a disorder of perceiving and relating to others (Skodol, 2012). The importance of how perceptions of others are organized (or perhaps distorted) and its impact on personality pathology is highlighted in several literatures including cognitive-behavioral (Beck, Freeman, David, & Assocciates, 2004), interpersonal (Leising & Borkenau, 2011; Pincus & Hopwood, 2012), psychodynamic (Bornstein, Denckla, & Chung, 2012), self-other agreement and person perception (Oltmanns & Turkheimer, 2006), and attachment (Shorey, 2010) theories of personality and psychopathology, as well as the integrative Cognitive-Affective Processing System (CAPS) approach to personality and adjustment (Eaton, South, & Kreuger, 2009; Kammrath, 2011). Examining the covariation of interpersonal perception in personality pathology could provide a useful new way to describe how such individuals organize their social experiences in the natural world.…”
mentioning
confidence: 99%